Lexical Bundles in L1 and L2 English Academic Writing: Convergent and Divergent Usage - Yan Li; Hong Lei (SAGE Open)
As a key component of fluent linguistic production, multi-word sequences called lexical bundles are considered an important distinguishing feature of discourse in different registers, genres, and disciplines. They are also an important aspect of empirically correct and proficient language use in a corpus of natural language because they enable writers to establish membership in a specific discourse community. Given the significant role of lexical bundles in academic writing, the comparison of master’s theses, written by L1 English and L2 English master’s students, offers significant insight into the ways in which lexical bundles are utilized, both structurally and functionally. Based on the assumption, we built a 1,282,700-word English corpus of master’s theses to compare the convergent and divergent usage of four-word lexical bundles in the academic texts of L1 English and L1 Chinese of L2-English writers. Findings showed that Chinese students use lexical bundles more frequently but with less variety than L1 English writers. Shared bundles, which exhibit a grammatically compressed discourse style dominated by prepositional phrases, were used by the two groups of writers in different ways and with significantly different frequencies. The analysis of divergent bundles revealed that Chinese writers frequently use clausal bundles while L1 English students employ more phrasal bundles. With regard to students’ ability to write convincingly in various functional categories, the two groups exhibited remarkable differences. Chinese writers also demonstrated some uniqueness of lexical bundles usage and weak awareness of register in the academic writing. The pedagogical implications and further areas of the study are discussed.